Fosil Polen Mangrove Berumur Pliosen Dari Formasi Tapak Daerah Kedung Randu, Banyumas - Agung Suedy, Sri Widodo; Muhadiono, Muhadiono; Sabiham, Supiandi; Qoyim, Ibnul (Bioma : Berkala Ilmiah Biologi, 2012)
Thirty sediment samples had been taken from the Tapak Formation of Kedung Randu areas, Banyumas, to reconstruct the diversity of mangrove flora from this area the past. This samples were processed for palynological slides used standard palynology preparation method. The microscopic identification of palynomorphs were done to identify taxa of paleoflora. Fifty-six types of pollen and spores fossils had been identified and 22 types were mangrove pollen-spores fossils. This fossils could be grouped into major mangrove (Zonocostites ramonae/Rhizophora type, Spinizonocolpites echinatus/Nypa fruticans, Florschuetzia levipoli/Soneratia caseolaris and Avicennia type); group of minor mangrove (Retitricolporites sp./Excoecaria sp., Discoidites novaguenensis/Brownlowia type, Camptostemon and Acrostichum aureum), and a group of plant associations (Retitricolporites equatoralis/Calophyllum type, Dicolpopollis sp./Calamus type, Racemonocolpites sp./Oncosperma, Marginipollis concinus/Barringtonia, Pandaniidites sp. /Pandanus, Terminalia catappa, Ilexpollenites sp./Ilex, Stellatopollis sp./Croton type, Acanthaceae type, Cyperaceaepollis/Cyperaceae, Podocarpidites/Podocarpus, Aglaia type, Haloragacidites/ Casuarina and Verrucatosporites usmensis/Stenochlaena palustris. Stenochlaeniidites papuanus and Podocarpus imbricatus were found in the samples. Tapak Formation was included in the last section of the Podocarpus imbricatus/Dacrycarpidites australiensis Zone of Java Palynological Zonation, and this formation was in the age of Late Pliocene towards Pleistocene.Â Key word: Tapak Formation; major-minor-plant associations of mangrove; palynological zonation